2011
DOI: 10.1111/j.1365-2966.2011.19925.x
|View full text |Cite
|
Sign up to set email alerts
|

Local stellar kinematics from RAVE data - II. Radial metallicity gradient

Abstract: We investigate radial metallicity gradients for a sample of dwarf stars from the RAdial Velocity Experiment (RAVE) Data Release 3 (DR3). We select a total of approximately 17 000 F‐type and G‐type dwarfs, using a selection of colour, log g and uncertainty in the derived space motion, and calculate for each star a probabilistic (kinematic) population assignment to a thick or thin disc using space motion and additionally another (dynamical) assignment using stellar vertical orbital eccentricity. We additionally … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
40
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 50 publications
8
40
2
Order By: Relevance
“…The orbital elements for a star used in our work are the mean of the corresponding orbital elements calculated over 15 orbital periods of that specific star. The orbital integration typically corresponds to 3 Gyr and is sufficient to evaluate the orbital elements of solar suburb stars (Coşkunoglu et al 2012;Bilir et al 2012;Duran et al 2013). Table 1.…”
Section: Local Stellar Kinematics From Rave Data -V Kinematic Investmentioning
confidence: 99%
“…The orbital elements for a star used in our work are the mean of the corresponding orbital elements calculated over 15 orbital periods of that specific star. The orbital integration typically corresponds to 3 Gyr and is sufficient to evaluate the orbital elements of solar suburb stars (Coşkunoglu et al 2012;Bilir et al 2012;Duran et al 2013). Table 1.…”
Section: Local Stellar Kinematics From Rave Data -V Kinematic Investmentioning
confidence: 99%
“…The full set of RAVE chemo-kinematical data was recently used by Boeche et al (2013) to study the relation between abundances and kinematics of the Galactic disc populations. The radial metallicity gradient was previously studied in recent works by using RAVE data (Karataş & Klement 2012;Coşkunoǧlu et al 2012), but none of them investigated the gradients for the individual elemental abundances. Recently, Bilir et al (2012) split a sample of red-clump RAVE stars into thin-and thick-disc subsamples by labelling the stars as a function of their kinematic characteristics, and measured the metallicity gradients in these subsamples.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical gradients found by previous investigations can span quite a wide range (from −0.029 dex kpc −1 by Andrievsky et al 2002 using Cepheids, to −0.17 dex kpc −1 by Sestito et al 2008 using open clusters). Most of the works seem to converge on a value close to ∼−0.06 dex kpc −1 by using different tracers (Cepheids by Luck et al 2006;Luck & Lambert 2011;Yong et al 2006;Lemasle et al 2008 among others; open clusters by Friel et al 2002;Sestito et al 2008;Pancino et al 2010 among others; planetary nebulae by Pasquali & Perinotto 1993;Maciel & Quireza 1999; main-sequence turn-off stars by Cheng et al 2012;Coşkunoǧlu et al 2012). It has been shown that the radial gradient becomes flatter with increasing distance from the Galactic plane (Pasquali & Perinotto 1993;Boeche 2011;Cheng et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A good representation of the Milky Way is obtained with the superposition of these components. The orbital period of the LSR is taken P = 2.18 × 10 8 years while V c = 222.5 km s −1 represents the circular rotational velocity at the Solar Galactocentric distance, R 0 = 8 kpc (Coşkunoglu et al 2012;Bilir et al 2012). …”
Section: Population Analysismentioning
confidence: 99%